ANALISIS PENGARUH KEPEMILIKAN TERKONSENTRASI DAN ASIMETRI INFORMASI TERHADAP PENERAPAN KONSEP KONSERVATISME AKUNTANSI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018 - Novita Eka P.; Mukhzarudfa Mukhzarudfa; Yudi Yudi (Jurnal Akuntansi & Keuangan Unja, 2021)
This study aims to analyze the effect of insider, outsider concentrated ownership, and information asymmetry on the application of the concept of accounting conservatism either partially or simultaneously. The population in this study were companies listed on the IDX in 2018, 648 companies. Sampling technique used in this study was purposive sampling, sample of 70 companies. With the data analysis technique used is through multiple linear regression equations with SPSS. The results showed that partially outsider concentrated ownership and information asymmetry had a positive and significant effect on the application of the concept of accounting conservatism. Meanwhile, insider concentrated ownership has no effect on the application of the accounting conservatism concept. Simultaneous testing it can be concluded that insider, outsider concentrated ownership, and information asymmetry together have a positive and significant effect on the application of the concept of accounting conservatism. Where the magnitude of the influence of Insider Ownership, Outsider Ownership, and Information Asymmetry on the application of the concept of accounting conservatism is 42.6%, while the remaining 57.4% is influenced by other variables that are not careful in this study.